2021
DOI: 10.1016/j.celrep.2021.108940
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral drug screen identifies DNA-damage response inhibitor as potent blocker of SARS-CoV-2 replication

Abstract: SARS-CoV-2 has currently precipitated the COVID-19 global health crisis. We developed a medium-throughput drug screening system and identified a small molecule library of 34 of 430 protein kinase inhibitors that were capable of inhibiting SARS-CoV-2 cytopathic effect in human epithelial cells. These drug inhibitors are in various stages of clinical trials. We detected key proteins involved in cellular signaling pathways mTOR-PI3K-AKT, ABL-BCR/MAPK, and DNA-Damage Response that are critical for SARS-CoV-2 infec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 79 publications
4
97
0
Order By: Relevance
“…Its cytotoxicity is probably caused by inhibition of this compound's original cellular target Akt as Akt signalling is shown to be important for cell survival ( Figure 5B,C and Supplementary Figure S11A) [ 55 ]. Interestingly, PI3K/Akt/mTOR signalling inhibition has been demonstrated to suppress SARS-CoV-2 replication in mammalian cells [ 62 , 63 ]. From the current study, we cannot elucidate whether FPA-124 inhibits viral growth by inhibiting nsp13 activity, modulating Akt signalling or a combination of both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Its cytotoxicity is probably caused by inhibition of this compound's original cellular target Akt as Akt signalling is shown to be important for cell survival ( Figure 5B,C and Supplementary Figure S11A) [ 55 ]. Interestingly, PI3K/Akt/mTOR signalling inhibition has been demonstrated to suppress SARS-CoV-2 replication in mammalian cells [ 62 , 63 ]. From the current study, we cannot elucidate whether FPA-124 inhibits viral growth by inhibiting nsp13 activity, modulating Akt signalling or a combination of both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Human ACE2 coding sequence was cloned into a lentiviral vector as described (Garcia et al, 2021). sgRNAs targeting human ORAI1 (Forward primer: CACCGGATCGGCCAGAGTTACTCC ; Reverse primer: AAACCGGAGTAACTCTGGCCGATCC ) and human STIM1 (Forward primer: CACCGTGAGGATAAGCTCATCAGCG ; Reverse Primer: AAACCGCTGATGAGCTTATCCTCAC ) genes were subcloned into pLentiguide puro (Addgene).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, hPSCs have already shown great promise in several SARS-CoV-2 studies focused on the lungs, heart, gut, and pancreas [ 78 ]. For example, in combination with in vivo and in silico models, hPSC-CMs have demonstrated significant value in elucidating the mechanisms of viral entry, cell death, and cytokine storm for indirect effects related to SARS-CoV-2 infection in neighboring cells and organs [ 40 , 92 , 95 97 ]. In addition, hPSCs exhibit powerful implications for SARS-CoV-2 clinical studies involving cell therapy or high throughput drug screening.…”
Section: Discussionmentioning
confidence: 99%
“…hPSC-CMs have also shown strong potential as model for assessing the cardiac safety of new drugs against SARS-CoV-2 [ 94 ]. Several reports have used hPSC-CMs to investigate SARS-CoV-2 infection in clinical perspectives [ 95 97 ]. Marchiano et al indicated that SARS-CoV-2 infection changed the electrophysiological properties of hPSC-CMs by decreasing electrical conduction velocity and depolarization spike amplitude [ 96 ].…”
Section: Human Stem Cell-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation